Evaluation of Cr(VI) Reducing Capability of Bacillus licheniformis DAS1 Using a Multifactor Experimental Approach - Md. Saduzzaman, Kumari Mini, Shardendu Shardendu and S. Rehan Ahmad (Nature Environment and Pollution Technology, 2023)
The current study is about detoxifying soil and water contaminated with toxic Cr(VI). To ensure that DAS1 could develop as well as possible, the pH was changed between 4 and 10. DAS1 showed its highest growth at pH 8, and at the same pH, it had an 85% potential to remediate by converting Cr(VI) to Cr(III). Immobilized bacteria increased the reduction of Cr(VI) to Cr(III) from the culture medium to 90.4%. The impact of glucose concentrations between 0.5 and 2.5 g.L-1 was examined. The greatest development was seen at pH 8 and 2 g.L-1 glucose concentration. The remediation potential was improved by up to 96% when the growing medium contained 200 mg.L-1 Cr(VI). The value of ks (0.434 g.L-1) demonstrated the substrate’s affinity for bacteria in accordance with the Monod equation, while μ max (0.090 h) demonstrated that DAS1 required 11.11 h for maximal growth. The multifactor experimental design was used to analyze mixed cultures of DAS1 and DAS2 in a 1:1 ratio, and it was determined that the X3Y2Z1 experiment design was best for completely removing Cr(VI) from the growing medium. By making pores using Na2EDTA, it was determined that the cell membrane’s impermeability did not cause Cr(VI) resistance in DAS1. The delayed lag phase indicated that the enzyme activity was inductive rather than constitutive.